(untitled) (COLOMBIAN JOURNAL OF ADVANCED TECHNOLOGIES, 2023)
Non-fungible tokens are one of the topics that have been most popular in recent months due to the high sums of money that their transactions have represented; However, there are many questions about what non-fungible tokens are and how they work. In this way, this study is developed in order to analyze the benefits of non-fungible Tokens and their application within the various markets. For the development of the study, a systematized bibliographic review carried out in the WoS and Scopus databases is presented, accompanied by a bibliometric analysis of the results of the search equation before carrying out the process of filtering the results. The results obtained show an important level of application of non-fungible tokens in various sectors, based on the qualities of providing verifiable and unclonable information to various assets; which can range from physical devices based on the IOT to digital art, music or collectibles within video games. It is concluded that the panorama of non-fungible tokens, although very uncertain, shows a trend towards growth and permanence as a type of asset to be considered in the development of the 4.0 era.